Combination of inflammatory and amlodipine induced gingival overgrowth in a patient with cardiovascular disease - Pasupuleti, Mohan Kumar; Musalaiah, S. V. V. S.; Nagasree, M; Kumar, P Aravind (Avicenna Journal of Medicine, 2013)
Gingival overgrowth (GO) is among one of the most important clinical features of gingival pathology frequently seen in periodontal clinic. Amlodipine is a comparatively new calcium channel blocker and is being used with increasing frequency in the management of hypertension and angina. A 48-year-old Indian woman who was on amlodipine for 3 years for hypertension reported to the department of periodontics with the complaint of swollen, un esthetic gums. The patient developed GO 6 months before her first visit to dental hospital. She developed GO very rapidly due to the increase in amlodipine dose due to the severe angina attack 6 months before and due to the use of cholesterol (CHO) lowering drug. The main aim of the case report is to study the severity of amlodipine induced GO in a patient with cardiovascular disease (CVD) and to identify the role of subgingival microorganisms on inflammatory gingival enlargement in the same patient. The severity and rapidity of gingival enlargement in this report could have been triggered by doubling the dose of amlodipine and concomitant use of CHO lowering drug.
Keywords: Acute myocardial infarction; amlodipine; angina; gingival overgrowth